Effects of Boron Nutrition and Water Stress on Nitrogen Fixation, Seed δ15N and δ13C Dynamics, and Seed Composition in Soybean Cultivars Differing in Maturities - Nacer Bellaloui; Alemu Mengistu (The Scientific World Journal)
Therefore, the objective of the current research was to investigate the effects of foliar B nutrition on seed protein, oil, fatty acids, and sugars under water stress conditions. A repeated greenhouse experiment was conducted using different maturity group (MG) cultivars. Plants were well-watered with no foliar B (W − B), well-watered with foliar B (W + B), water-stressed with no foliar B (WS − B), and water-stressed with foliar B (WS + B). Foliar B was applied at rate of 0.45 kg·ha−1 and was applied twice at flowering and at seed-fill stages. The results showed that seed protein, sucrose, fructose, and glucose were higher in W + B treatment than in W − B, WS + B, and WS − B. The increase in protein in W + B resulted in lower seed oil, and the increase of oleic in WS − B or WS + B resulted in lower linolenic acid. Foliar B resulted in higher nitrogen fixation and water stress resulted in seed δ15N and δ13C alteration. Increased stachyose indicated possible physiological and metabolic changes in carbon and nitrogen pathways and their sources under water stress. This research is beneficial to growers for fertilizer management and seed quality and to breeders to use 15N/14N and 13C/12C ratios and stachyose to select for drought tolerance soybean.